MARKET ANALYSIS OF SHOP-OFFICES DEVELOPMENT: A CASE STUDY IN RAWANG, MALAYSIA - Ashwadi Ashraf Mazlan; Fathullah Hazim Nisfuazmi; Muhammad Afiq Zulkupli; Muhammad Alif Putra Aaftab Alam; Muhammad Aiman Hakiem Musliandi; Noryanto Asroun Mohamad Asroun (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Lack of demand-supply studies, inadequate understanding of local demographics, and speculative development have all played critical roles in the increasing number of unsold shop-offices. The main objectives of this study are to assess the current and future demand and supply of 2-storey shop-offices and to evaluate the proposed development through a comprehensive SWOT analysis. This study adopts a quantitative research method and relies on secondary data sources. The collected data was analyzed by frequency and changes to provide descriptive statistics. The demand and supply analysis shows that the proposed development is currently in demand when it has the highest number of transactions, but lacks completion and project starts in the past few years. However, the new planned supply of 2-storey shop-offices will be the competitors to the proposed development in the future. Furthermore, SWOT analysis found that the proposed development has many strengths, opportunities, and threats but with minimum weaknesses.